Particle Size Distribution and Its Relationship to Black Carbon in Two Urban and One Rural Site in Santiago de Chile - Rubio-Campos, M; Gramsch-Labra, E; Perez-Jara, P (Taylor and Francis Inc., 2014)
The size distribution of particles has been studied in three sites in the Metropolitan area of Santiago de Chile in the winter of 2009 and a comparison with black carbon was performed. Two sites are located near busy streets in Santiago and the other site is located in a rural area about 40 km west of Santiago with little influence from vehicles, but large influence from wood burning. The campaign lasted 1 or 2 weeks in each site. We have divided the particle size measurements into four groups (10–39 nm, 40–62 nm, 63–174 nm, and 175–700 nm) in order to compare with the carbon monitor. In the sites near the street, black carbon has a high correlation (R 0.85) with larger particles (175–700 nm). The correlation decreased when black carbon was compared with smaller particles, having very small correlation with the smallest sizes (10–39 nm). In the rural site, black carbon also has a high correlation (R = 0.86) with larger particles (175–700 nm), but the correlation between black carbon and the finest particles (10–39 nm) decreases to near 0. These measurements are an indication that wood burning does not generate particles smaller than ~50 nm. In the urban sites, particle size distribution is peaked toward smaller particles (10–39 nm) only during rush hours, but at other times, particles size distribution is peaked toward larger sizes. When solar radiation was high, evidence of secondary particle formation was seen in the rural site, but not in the urban sites. The correlation between the number of secondary particles and solar radiation was R2 = 0.46, indicating that it there may be other variables that play a role in ultrafine particle formation. Implications: A study of the size distribution of particles and black carbon concentration in two street sites and one rural site shows that in the last site the number of particles ultrafine particles (d < 40 nm) is 10 times lower but the number of larger particles is about 2 times lower. Thus, the rural site has less of the particles that are more dangerous to health. The number of ultrafine particles is mostly associated with traffic, while the number of larger particles is associated with wood burning and other sources.Wood burning does not generate particles smaller than ~50 nm. © 2014 A&WMA.